2017
DOI: 10.1016/j.jes.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and factors affecting levels of airborne and water bromoform in chlorinated seawater swimming pools

Abstract: Water and air quality of eight seawater swimming pools using chlorine disinfection was measured during four sampling campaigns, spread on one full-year, and in four thalassotherapy centers located in Southeast of France. Concentrations of trihalomethanes (THMs) in air and in water as well as concentrations of parameters, including nonpurgeable organic carbon (NPOC), free residual chlorine (Cl), pH, Kjeldhal Nitrogen (KN), salinity, conductivity, bromide ions and, water and air temperature, were measured. Water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Bromoform is the most abundant trihalomethane (THM) compound in seawater swimming pools, and measured levels of bromoform (CHBr 3 ) in those kinds of pools are particularly alarming. Consequently, it seems important to determine the occupants exposure to bromoform (and to the other THM), not only in water but also in air 164 . The measured values of bromoform exceeded frequently the recommended value of 350 µg/m 3 201…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bromoform is the most abundant trihalomethane (THM) compound in seawater swimming pools, and measured levels of bromoform (CHBr 3 ) in those kinds of pools are particularly alarming. Consequently, it seems important to determine the occupants exposure to bromoform (and to the other THM), not only in water but also in air 164 . The measured values of bromoform exceeded frequently the recommended value of 350 µg/m 3 201…”
Section: Resultsmentioning
confidence: 99%
“…In indoor chlorinated swimming pool facilities located in Southern Europe, the reported mean concentration of indoor bromoform (CHBr 3 ), dibromochloromethane (CHClBr 2 ), chloroform (CHCl 3 ), and bromodichloromethane (CHBrCl 2 ) was 0.4 µg/m 3 ‐11.2 µg/m 3 ; 1.9 µg/m 3 ‐13.2 µg/m 3 ; 35.0 µg/m 3 ‐54.5 µg/m 3 ; and 4.2 µg/m 3 ‐14.6 µg/m 3 , respectively 165,179 . In indoor seawater swimming pools located in France, the reported mean concentration of indoor bromoform (CHBr 3 ) and dibromochloromethane (CHClBr 2 ) were 200 µg/m 3 (max 1600 µg/m 3 ) and 13 µg/m 3 (max 150 µg/m 3 ), respectively 164,172 . Bromoform is the most abundant trihalomethane (THM) compound in seawater swimming pools, and measured levels of bromoform (CHBr 3 ) in those kinds of pools are particularly alarming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure demonstrates that salinity does not play a significant role in MIMS analysis. However, the maximum salt concentration tested here does not ensure the absence of interference in the particular case of seawater swimming pools, where salt concentration can reach 20 g.L −1 . At higher NaCl concentrations (5,8–58 g.L −1 ), Miranda et al reported ionic strength dependence of MIMS signals for the quantification of four gases.…”
Section: Resultsmentioning
confidence: 99%